Wanderungen eines Ortes Das Gelände der alten Messe ("Staro Sajmište"), Belgrad - Saiger, Magdalena (Südosteuropäische Arbeiten, 2023)
Places and spaces are often considered to be static and immobile when compared with the dynamism of time. This volume challenges that notion, positing a theory of the mobility of places by tracing the changing localizations of the Old Fairground at the heart of the Serbian capital of Belgrade. This paints a multifaceted picture of the "journeys" that this contentious site of memory has embarked upon.